Update on the Use of Transcranial Electrical Brain Stimulation to Manage Acute and Chronic COVID-19 Symptoms - Pilloni, Giuseppina; Bikson, Marom; Badran, Bashar W.; George, Mark S.; Kautz, Steven A.; Okano, Alexandre Hideki; Baptista, Abrahão Fontes; Charvet, Leigh E. (Frontiers in Human Neuroscience, 2020)
The COVID-19 pandemic has resulted in the urgent need to develop and deploy treatment approaches that can minimize mortality and morbidity. As infection, resulting illness, and the often prolonged recovery period continue to be characterized, potential therapeutic roles for transcranial electrical stimulation (tES) have emerged as promising non-pharmacological interventions. tES techniques have established therapeutic potential for managing a range of conditions relevant to COVID-19 illness and recovery, and may further be relevant for the general management of increased mental health problems during this time. Furthermore, these tES techniques can be inexpensive, portable, and allow for trained self-administration. Here, we summarize the rationale for using tES techniques, specifically transcranial Direct Current Stimulation (tDCS), across the COVID-19 clinical course, and index ongoing efforts to evaluate the inclusion of tES optimal clinical care.